Dependence of Melting Process on Size and Edge Type of Graphene Nanoribbon - Hang, Nguyen Thi Thuy (Communications in Physics, 2017)
The study of variation of the size, armchair and zigzag types effects on the melting process of graphene nanoribbon. A numerical  thermodynamical model has been devoted for the study. The phase transition has first order behaviour. The formation of different defects, ring size and coordination number is dependent on the size and the edge type of GNR. The nuclei of heating appear at temperature around 2300K and that can be considered as pre-melting point. The melting process shows the case that the results of Berezinsky-Kosterlitz-Thouless-Nelson-Halperin-Young (BKTNHY) theory cannot be applied.